EFFECT OF GOVERNMENTAL ANNOUNCEMENT AND DECISIONS DURING COVID-19 ON INDONESIAN SECTORAL INDEXES - Irshad Adriatama; Raden Aswin Rahadi (Jurnal Manajemen dan Kewirausahaan, 2021)
Global economy is suffering from a crisis due to COVID-19, during few months after the virus had begun to spread stock prices had been falling drastically all over the world. This paper aim to analyze what is happening to the stock market in Indonesia during the period of COVID-19 pandemic. The analysis will be done by looking at the historical data of several composite index from different sectors during the period of pandemic. We will take notes of important dates during this pandemic such as: first confirmed case, first death, work-from-home policy date, and other dates, to see whether these events can affect the index price during this pandemic by analyzing abnormal return on a certain period near those dates.